Aging, Diabetes, Obesity, and Cognitive Decline: A Population‐Based Study. Issue 5 (4th February 2020) - Ganguli, Mary; Beer, Joanne C.; Zmuda, Joseph M.; Ryan, Christopher M.; Sullivan, Kevin J.; Chang, Chung‐Chou H.; Rao, R. Harsha
Abstract : BACKGROUND/OBJECTIVES: To investigate potential mechanisms underlying the well‐established relationship of diabetes and obesity with cognitive decline, among older adults participating in a population‐based study. DESIGN/SETTING: Ten‐year population‐based cohort study. PARTICIPANTS: A total of 478 individuals aged 65 years and older. MEASUREMENTS: We assayed fasting blood for markers of glycemia (glucose and hemoglobin A1c [HbA1c]), insulin resistance (IR) (insulin and homeostatic model assessment of IR), obesity (resistin, adiponectin, and glucagon‐like peptide‐1), and inflammation (C‐reactive protein). We modeled these indices as predictors of the slope of decline in global cognition, adjusting for age, sex, education, APOE*4 genotype, depressive symptoms, waist‐hip ratio (WHR), and systolic blood pressure, in multivariable regression analyses of the entire sample and stratified by sex‐specific median WHR. We then conducted WHR‐stratified machine‐learning (Classification and Regression Tree [CART]) analyses of the same variables. RESULTS: In multivariable regression analyses, in the entire sample, HbA1c was significantly associated with cognitive decline. After stratifying by median WHR, HbA1c remained associated with cognitive decline in those with higher WHR. No metabolic indices were associated with cognitive decline in those with lower WHR. Cross‐validated WHR‐stratified CART analyses selected no predictors in participants older than 87 to 88 years. Faster cognitive decline was associated, in lower WHR participants younger than 87 years, with adiponectin of 11 or greater; and in higher WHR participants younger than 88 years, with HbA1c of 6.2% or greater. CONCLUSIONS: Our population‐based data suggest that, in individuals younger than 88 years with central obesity, even modest degrees of hyperglycemia might independently predispose to faster cognitive decline. In contrast, among those younger than 87 years without central obesity, adiponectin may be a novel independent risk factor for cognitive decline. J Am Geriatr Soc 68:991–998, 2020